Analysis spiritual intelligence of IAIN Bone students in learning in the covid-19 period - Ahmad Irfan (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This study aims to determine the relationship between online learning systems during the Covid-19 period and spiritual intelligence. This research is qualitative research. This research was conducted at the Bone State Islamic Institute. Data collection techniques in this study were carried out by observation, interviews, and documentation. The data that has been obtained is then analyzed by conducting three stages of data analysis, namely reducing data, data models and verifying conclusions. The results of this study show that the spiritual intelligence of IAIN Bone students in learning before Covid-19 students are able to interpret the substance of learning so as to make them focus on their life goals; and learning during Covid-19 is influenced by the application of an online learning system that makes some students still able to interpret the substance of learning so that they remain focused on their goals in learning, although there are some other students who have not been optimal in interpreting the substance of learning that can make them focus on their life goals.